The Essential Things for Victims of Terrorism in Indonesia: Medical Assistance, Psychosocial and Psychological Rehabilitation - Ramadianto, Anang Riyan (Faculty of Law Universitas Negeri Semarang, 2023)
Terrorism is a crime that endangers the security, peace and welfare of people while posing a severe threat to the sovereignty of every nation. This was inextricably linked to the suffering of victims of terrorism-related crimes, who needed the government to provide them with legal protection. The study aims to analyze and compare some cases concerning how victims of terrorist crimes in Indonesia are protected by the law, particularly with regard to medical assistance, psychosocial and psychological rehabilitation. With a legal empirical methodology and descriptive analytical research criteria, this study used qualitative research techniques. The study was carried out in Jakarta at the National Counterterrorism Agency. Primary data and secondary data are also used. Using interviews and a literature review, the data is collected. The data were reduced, displayed, and categorize using the methods described above. using qualitative analytical techniques to provide data as narrative text descriptions. According to the study's findings, there are advantages and disadvantages to Indonesia's legal protection of those who have been victims of terrorist crimes. One issue is that the filing deadline for claims made on behalf of those who have already been victims of terrorism crimes is only June 22, 2021. The legal protection of victims of terrorist crimes is hampered by a number of reasons in Indonesia’s legal protection of those who have been the victims of terrorist crimes.